Demystify False Dilemmas to Speak About Corruption in Health Systems: Different Actors, Different Perspectives, Different Strategies; Comment on "We Need to Talk About Corruption in Health Systems" - Karen Hussmann (Kerman University of Medical Sciences, 2019)
The call of the editorial of the International Journal of Health Policy and Management regarding the "Need to talk about corruption in health systems" is spot on. However, the perceived difficulties of why this is so should be explored from an actor's perspective, as they differ for government actors, donors and the research community. In particular, false dilemmas around definition problems should be demystified, including by building systematic bridges between the anti-corruption/integrity and health policy communities of practice. In addition, the focus on corruption in frontline health service delivery generating mainly problems of access to health, needs to be complemented with addressing sophisticated kickback schemes, nepotism, and state capture of legislative and regulatory agencies and processes draining the health systems of large amounts of resources leading to another false dilemma of assumed sector underfunding. In terms of what can be done, comprehensive corruption experience and risk assessments conducted by independent actors, eg, universities, aimed at generating some basic consensus among the different actors of priority areas to be addressed on the basis of a co-responsibility approach could provide the basis for reform. Finally, governments and private sector actors in countries characterized by systemic corruption and clientelistic political systems will not reform themselves without strong and sustained demand from civil society and the media.